A markovian approach to determine optimal means for SME production process - Hasan Basari, Abd Samad; Hussin, Burairah; Asmai, Siti Azirah; Ibrahim, Nuzulha Khilwani; Shibghatullah, Abdul Samad (2011)
The determination of optimum process mean has become one of the focused research area in order to improve product quality. Depending on the value of quality characteristic, an item can be reworked, scrapped or accepted by the system which is successfully transform to the finishing product by using the Markovian model. By assuming the quality characteristic is normally distributed, the probability of rework, scrap and accept is obtained by the Markov model and next the optimum of process mean is determine which maximizes the expected profit per item. In this paper, we present the preliminary analysis of selecting the process mean by referring to SME production process. By varying the rework and scrap cost, the analysis shows the sensitivity of the Markov approach to determine process mean.